2018
DOI: 10.1177/1940082918762372
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Taxonomic, Structural, and Functional Diversity to Local-Scale Environmental Variation in Afromontane Forests in South Africa

Abstract: Exploring taxonomic, functional, and structural diversity can provide additional insights into our understanding of diversity responses to environment. Using altitude, slope, and relative radiation index as well as floristic and functional data from a South Africa Afromontane forest, we examined how taxonomic, structural, and functional diversity varied with local environmental variation. Taxonomic and structural diversity were quantified through species richness-and diameter class-based Shannon index and even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
3
15
0
1
Order By: Relevance
“…There are two important components in the silt-sand-rocky soils: the rocks that form the undulating relief and the silt resulting from a soil degradation-transport-deposit process. Thus, our results align with the ideas that species structures are environment structured (Mensah, Salako, et al, 2018) and indicate that local environmental variation played a substantial role in A. africana recruitment and growth. Gambiza (2001) reported that the patchy distribution of the soil types and topographic features modify plant-available moisture and available nutrients, thereby influencing plant structure.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…There are two important components in the silt-sand-rocky soils: the rocks that form the undulating relief and the silt resulting from a soil degradation-transport-deposit process. Thus, our results align with the ideas that species structures are environment structured (Mensah, Salako, et al, 2018) and indicate that local environmental variation played a substantial role in A. africana recruitment and growth. Gambiza (2001) reported that the patchy distribution of the soil types and topographic features modify plant-available moisture and available nutrients, thereby influencing plant structure.…”
Section: Discussionsupporting
confidence: 88%
“…Yang, Fan, Li, and Ko (2018) highlighted that slope influenced tree growth through displacement of eroded soil material, water, and plant debris. Our finding is partly supported by Mohammed (2014) and Mensah, Salako, et al (2018) who showed that topographical variation mainly slope can affect tree structure. Typically, steeper slopes and gravity-driven processes would challenge tree mechanical stability and growth.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Several theories have been developed to explain the relationship between biodiversity and carbon, of which niche complementarity and selection theories are mostly supported by the results of biodiversity-carbon studies in different habitats [2,18,19]. In a study on whether the species richness (count of species in a plot or community), functional diversity (variation of different traits between species, e.g., maximum canopy height, wood density) or structural diversity (variation of DBH in a plot or community) has a positive effect carbon storage, the niche complementarity effect is assumed to be effective in carbon storage [2,7,20]. The explanation behind this assumption is that niche complementary theory assumes that the ecosystem carbon capacity is mostly determined by the diverse coexisting species, with their greater trait variation in a community [2,21].…”
Section: Introductionmentioning
confidence: 98%